Software for evaluation of hydraulic and economic performances of center pivots - Ludwig, Rafael [UNESP]; Sampaio Neto, Givaldo Dantas; Putti, Fernando Ferrari [UNESP]; Saad, João Carlos Cury [UNESP] (My University, 2018)
Irrigated agriculture is dependent on electricity to increase production and to be able to supply the needs of the market, which is increasingly demanding and competitive. However, the lack of resources, such as water and electricity, and the rise of production cost, demand a rational use of these resources. The objective of this paper is to present the process of creating a software to assess the influence of land slope on pressures and energy spent in a center pivot irrigation system. The software was developed using Delphi programming language, accessing a database created in Access 2013, part of the Microsoft Office suite. It is a research developed in a partnership with the Rural Engineering Department of Faculdade de Ciências Agronômicas – FCA –UNESP, Escuela de Ingenieros Agronomos da Universidad Politécnica de Madrid – EIA-UPM, and Associação do Sudoeste Paulista de Irrigantes e Plantio na Palha – ASPIPP, located in the district of Campos de Holambra in Parapanema – SP. The results show that the software is an alternative for performance validation and operation of center pivot irrigation systems. Moreover, it allows users to analyze the possibility of intervention in the flow rate and pressure to reduce operational costs, providing three possibilities of intervention considering water depth provided and energy consumption.
Desenvolvimento de software para avaliação dos desempenhos hidráulico e econômico de pivôs centrais
Keywords: Energy consumption; Optimization; Sprinkle irrigation